The Relationship Between Incentive and Employees’ Job Performance - Alvine Jonathan; Elyzabeth Wijaya; Agus Susanto; Susanto Susanto (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
Employees are essential to the attainment of an organization's objectives, vision, and mission. Employees are essential to a business, hence the corporation must prioritize their requirements. Several issues arose. The employees' performance deteriorated because of insufficient remuneration. Several individuals did not fulfill their responsibilities punctually, leading to a reduction in their job output. The corporation offered incentives to improve their job performance. This research will investigate the correlation between incentives and employee work performance. The author will utilize all of them as a sample for this investigation. This procedure is termed census sampling. The study substantiates the efficacy of Variable X (incentive) and Variable Y (workers' job performance). The reliability test further validates the results' dependability. The correlation coefficient is 0.73. This indicates a robust correlation between incentives and employee work performance. The hypothesis test produced a score of 4.53, demonstrating that the tcount surpasses the ttable (2.101). Consequently, we may exclude the null hypothesis (H0), which posits that no correlation exists between incentives and employees' job performance. This indicates a substantial correlation between the incentive (variable X) and workers' job performance (variable Y). This research shows that a correlation exists between incentives and workers' job performance. The incentive was a contributing factor to the enhancement of employee performance, while other elements, such as working environment, also had a role.